Suitability assessment of carbonate rocks from the Kataraktis Passage Member of the Olonos-Pindos Zone (Ileia Prefecture, Western Greece) for industrial applications - Tseni, X.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2013)
The potential industrial uses of Maastrictian-Paleocene carbonate rocks from the Kataraktis Passage Member of Olonos-Pindos Zone from Ileia Prefecture are evaluated based on their petrographic and geochemical characteristics, as well as their physical properties. Moreover, inter-relationships of the physical properties and geochemical composition were determined using simple linear regression analysis, in order to establish their mutual interactions. Investigation of the petrographic and geochemical characteristics of carbonate rocks may contribute to their quality assessment for their use in industrial applications.